Legal Void Regarding Discretion In The Police and The Urgency of Its Reformulation - I Made Juni Artawan; Evita Isretno Israhadi (Dialog Legal: Jurnal Syariah, Jurisprudensi dan Tata Negara, 2026)
Discretion is an integral part of the authority of law enforcement officers in the modern state administration system, including within the Indonesian National Police. In the context of dynamic police duties and functions that often confront unexpected situations, discretion provides a means for officers to act swiftly to maintain public order and security. However, the use of discretion by the police also carries the potential for legal issues if not supported by a clear and measurable normative framework. The fundamental problem that arises is the indication of a legal vacuum or unclear boundaries and mechanisms for implementing such discretion, which have implications for the accountability of officers' actions in the field. The absence of detailed guidelines often leads to overlapping legal interpretations and opens up loopholes for abuse of authority. It raises an urgent need to reformulate the regulation of discretion in Indonesian police law to align with the principles of a state based on the rule of law that guarantee legal certainty, justice, and the protection of human rights. This research uses a normative juridical method, an approach that focuses on the study of primary and secondary legal materials, including laws, legal literature, and other relevant normative documents. This approach aims to analyze the concept of discretion in administrative law, evaluate applicable laws and regulations, and identify normative deficiencies in current police discretionary arrangements. With this framework, this research is expected to provide theoretical and practical contributions to the development of a more responsive and accountable police legal system